Strong Linear Correlation between CH3NH2 Molecular Defect and THz-Wave Absorption in CH3NH3PbI3 Hybrid Perovskite Thin Film - Inhee Maeng; Asuka Matsuyama; Jung-Ho Yun; Shenghao Wang; Chul Kang; Chul-Sik Kee; Masakazu Nakamura; Min-Cherl Jung (Nanomaterials, 2020)
To control the density of a CH3NH2 molecular defect, which strongly contributed to a significant THz-wave absorption property in the CH3NH3PbI3 hybrid perovskite thin film formed by the sequential vacuum evaporation method, we performed post-annealing processes with various temperatures and times. In the thin film after post-annealing at 110 °C for 45 min, the density of the CH3NH2 molecular defect was minimized, and CH3NH3I and PbI2 disappeared in the thin film after the post-annealing process at 150 °C for 30 min. However, the density of the CH3NH2 molecular defect increased. Moreover, the THz-wave absorption property for each thin film was obtained using a THz time-domain spectroscopy to understand the correlation between the density of a molecular defect and the THz-wave oscillation strength at 1.6 THz, which originated in the molecular defect-incorporated hybrid perovskite structure. There is a strong linear correlation between the oscillator strength of a significant THz-wave absorption at 1.6 THz and the CH3NH2 molecular defect density.